Science Teachers’ Perceptions of Factors Influencing Senior School Students’ Performance in STEAM - Luwoye, Akindeyi; Adeoye, Moses Adeleke; Afolabi, Ojo Kayode; Suleiman, Bilkisu Aliyu (Universitas Pendidikan Indonesia (UPI), 2023)
The perspectives maintained by scientific educators concerning the factors that influence the academic performance of senior high school students in the domains of STEAM have a significant impact on shaping the educational landscape in Kwara State, Nigeria. By addressing the existing limitations in research and comprehending the intricacies that affect students' accomplishments in STEAM subjects, educational practitioners and policymakers possess the potential to implement focused interventions aimed at augmenting the calibre of instruction and fostering a workforce that is well-prepared for the future. This study investigated science teachers’ perceptions of factors influencing senior school students’ performance in STEAM in Kwara State, Nigeria. This study was descriptive research of a survey type. A purposive sampling technique was used to select 81 science teachers from Kwara State. Four research questions were generated and answered using frequency count and percentage while three hypotheses formulated were tested using Chi-square at 0.05 level of significance. The instrument used was the researcher-designed titled Teachers Perception Factors Affecting Students’ Performance Questionnaire (TPFASPQ). Findings revealed that there was a significant difference between science teachers’ perceptions of factors influencing students’ performance in STEAM based on academic qualification, teaching experience and school location. The study concluded that language barriers and occasional pregnancy among female students are some of the social and cultural issues influencing their performance in STEAM. The study recommended that the government should make available standard laboratories and adequate equipment to enable effective teaching of STEAM and also school administrators should employ qualified science teachers and organize in-service training for the teachers.